Populizm a prawo zgromadzeń. Przykład Polski 2015–2019 roku z uwzględnieniem regulacji wprowadzającej zgromadzenie cykliczne - Górka, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article presents the current departure of governments and society from democratic liberal constitutionalism and the creation of new forms of constitutionalism connected with populism. Two patterns of W. Sadurski and P. Blokker present examples of these new forms of constitutionalism. The text raises the problem of the impact of populism on the interpretation of norms contained in the Constitution of the Republic of Poland. The article presents techniques used by ruling populists in Poland (the right-wing party — Law and Justice, PiS). Nowadays, populists use different interpretations of undefined norms by trying to move away from the traditional interpretation, developed since the parliament has resolved the Basic Law. They use statutory references by which the law is created, often unconstitutionally. Populist activities are evidenced by means of P. Blokker’s pattern for the example of the right to assembly in Poland. The article shows the objectives of the amendment to the Bill — the Right of assembly. This act has created a new type of cyclical assembly. The text answers why and what aim they wanted to achieve by this amendment. At the end of the article, it shows the case related to the cyclical assembly — the dispute between the Inter-Enterprise “NSZZ” Solidarność and the City of Gdańsk of Solidarity Square as part of the celebration of the 30th anniversary of the partly free elections of 1989.
Keywords: populism; constitution; constitutionalism; liberal constitutionalism; interpretation; right to assembly; cyclical assembly